Kubernetes cookbook - Naik, Sameer; Goasguen, Sébastien; Michaux, Jonathan (O'Reilly Media, Inc., 2023)
Kubernetes is the de facto standard for container orchestration and distributed applications management across a microservices framework. With this practical cookbook, you'll learn hands-on Kubernetes recipes for automating the deployment, scaling, and operations of application containers across clusters of hosts. In this fully updated second edition, Sameer Naik, Sébastien Goasguen, and Jonathan Michaux from TriggerMesh provide a problem-solution-discussion format with easy lookups to help you find the detailed answers you need-fast. Kubernetes lets you deploy your applications quickly and predictably, so you can efficiently respond to customer demand. This cookbook delivers the essential knowledge that developers and system administrators need to get there.